Enhanced or Weakened Western North Pacific Subtropical High under Global Warming? - He, Chao; Zhou, Tianjun; Lin, Ailan; Wu, Bo; Gu, Dejun; Li, Chunhui; Zheng, Bin (Scientific reports, 2015)
The Western North Pacific Subtropical High (WNPSH) regulates East Asian climate in summer. Anomalous WNPSH causes floods, droughts and heat waves in China, Japan and Korea. The potential change of the WNPSH under global warming is concerned by Asian people, but whether the WNPSH would be enhanced or weakened remains inconclusive. Based on the multi-model climate change projection from the 5th phase of Coupled Model Intercomparison Project (CMIP5), we show evidences that the WNPSH tends to weaken and retreat eastward in the mid-troposphere in response to global warming, accompanied by an eastward expansion of East Asian rain belt along the northwestern flank of WNPSH. Weakened meridional temperature gradient on the northern flank of WNPSH and the associated thermal wind account for the weakened WNPSH in the mid troposphere. We recommend the WNPSH be measured by eddy geopotential height ( He ) instead of traditionally used geopotential height, especially in climate change studies.